2019
DOI: 10.1038/s41524-019-0227-7
|View full text |Cite
|
Sign up to set email alerts
|

A property-oriented design strategy for high performance copper alloys via machine learning

Abstract: Traditional strategies for designing new materials with targeted property including methods such as trial and error, and experiences of domain experts, are time and cost consuming. In the present study, we propose a machine learning design system involving three features of machine learning modeling, compositional design and property prediction, which can accelerate the discovery of new materials. We demonstrate better efficiency of on a rapid compositional design of high-performance copper alloys with a targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(49 citation statements)
references
References 48 publications
(49 reference statements)
1
48
0
Order By: Relevance
“…One example in the recent applications in this area is a machine learning design system (MLDS) developed to search for copper alloys of high ultimate tensile strength (UTS) and electrical conductivity (EC) as target properties. [576] The results in this research have revealed the successful implementation of MLDS method in assisting inverse design of 8 new high-performance copper alloys with target UTS of 600 to 950 MPa and EC over 50 pct of International Annealed Copper Standards. A second example in this area, Wen et al [577] have developed a property oriented optimization strategy to search for large hardness as a desired property in Al-Co-Cr-Cu-Fe-Ni high entropy alloys (HEA).…”
Section: Machine Learning-assisted Alloy Microstructure and Propmentioning
confidence: 79%
“…One example in the recent applications in this area is a machine learning design system (MLDS) developed to search for copper alloys of high ultimate tensile strength (UTS) and electrical conductivity (EC) as target properties. [576] The results in this research have revealed the successful implementation of MLDS method in assisting inverse design of 8 new high-performance copper alloys with target UTS of 600 to 950 MPa and EC over 50 pct of International Annealed Copper Standards. A second example in this area, Wen et al [577] have developed a property oriented optimization strategy to search for large hardness as a desired property in Al-Co-Cr-Cu-Fe-Ni high entropy alloys (HEA).…”
Section: Machine Learning-assisted Alloy Microstructure and Propmentioning
confidence: 79%
“…ML-based inverse design has attracted a great deal of attention for use in materials discovery [26][27][28][29][30] . The inverse design we were particularly interested in defines the prediction for an alloy composition, as well as the processing conditions required to accomplish a desired performance for a specific material.…”
mentioning
confidence: 99%
“…There has been considerable interest over the last few years in accelerating the process of materials design and discovery 1 . In the past decade, a new interdisciplinary research field called materials informatics, which combines data and information science with materials science, has led to an increasing number of successful materials discoveries [2][3][4][5][6][7] . Machine learning methods have played a key role in many of these studies.…”
Section: Introductionmentioning
confidence: 99%